Impact of Maturity Stage on Postharvest Quality of Strawberries Cold Stored for Fresh Consumption (Plant Bulletin, 2023)
Strawberries, being a non-climacteric fruit is usually harvested near maturity for optimal flavour and quality. However, this could also lead to a limited shelf life being highly perishable. However, the ripening stages could be a possible solution to minimizing the losses of post-harvest. Therefore, a current study was performed to evaluate the influences of ripening stages affecting the quality of strawberry fruit. Strawberry fruit was picked at four ripening stages unripe, semi-ripe, fully ripe and over-ripe maturity stages and stored at 5°C and were evaluated every alternate day for changes in fruit quality. The results concluded that red ripe fruits retained maximum fresh fruit weight and only 10%of fruit was un-marketable after 10 days of storage period. On the contrary, the highest decay rate was observed in over-ripe fruits and 50% of the fruit was unmarketable after 10 days of storage. Moreover, red ripe fruits were organoleptically more acceptable and retained higher total soluble solids whereas unripe and semi-ripe achieved low organoleptic scores due to higher total titratable acids. High levels of sugar in over-ripe fruits favoured a high incidence of pathogen attack. From this experiment, we can suggest that if fruits are picked at the red ripe stage will have optimal quality, moisture level, TSS, pH, TSS/acid ratio, TA, and good organoleptic score. Therefore, strawberry fruits for fresh eating should be picked at the red ripe maturity stage.
Keywords: Fragaria x ananassa; postharvest; maturity stage; fruit quality; Pakistan